ORE DEPOSITION RELATED TO THE SEPARATION OF THE LATE IMMISCIBLE FLUID PHASE OF MAGMA - Prokoptsev G.N.; Prokoptsev N.G. (My University, 1988)
We consider some features of the mechanism of magmatic ore formation, based on analysis of quenched textures of differentiated basalt melt. Our new data on the structure of quenched ore-silicate liquid generated at depth are presented. These data show that the textures of quenched basalt 'magma' reflect certain features of the mechanism of endogene separation of intratelluric fluid and its ore-forming role in magmatic bodies. The saturation of fluid differentiate with readily mobile components suggesting that, depending on external pressure, such fluid may separate either as a gas phase (under subaerial conditions) or as a high temperature hydrothermal solution.